The Contribution of Makhorijul Huruf Toward The Production of English Consonant - Hasani, Muhammad Zuhri; Sujarwati, Iis (Journal Analytica Islamica, 2024)
The design of this research is descriptive quantitative research which the backround in this thesis there is a difference in quality of pronounce of English consonant between the students have good makhorijul huruf with the students not good of makhorijul huruf. The purpose was to find out the contribution makhorijul huruf toward the production of English consonant for twelfth grade students at Madrasah Aliyah Ladang Panjang Sarolangun Academic Year 2023/2024. The subject of this research was twelfth grade students of Madrasah Aliyah Ladang Panjang academic year 2023/2024 there were ten students with details 4 men and 6 women. The data was collected by using oral test for all students. The results of research and discussion this research in the title the contribution of makhorijul huruf toward the production of English consonants for twelfth grade students Madrasah Aliyah Ladang Panjang Sarolangun Academic Year 2023/2024, by analyze normality test of makhorijul huruf that X2table value at 5% error level obtained with 9.488, while the X2count = 6.063 so that X2count< X2 table or 6.063 < 9.488, it can be concluded that the data of makhorijul huruf were normally distributed. And from the analysis of normality of pronunciation calculation that the value of X2table on error level of 5% was obtained with 9.488, while the X2count = 3.593 so the X2count < X2table or 3.593 < 9.488, it can be concluded that the data of Pronunciation were normally distributed. While the hypothesis test that the α 0:05 with dk = k-1 = 10-1 = 9 and ttable = 2.262. So thitung> ttable or 11,489> 2.62, then H0 is rejected and declared significant, so it can be declared significant. With Coefficient determinant or the magnitude contribution of makhorijul huruf toward the production of English consonants was 97.1%, this indicates that it is very valuable because the positive coefficient is very high contribution.